PENGARUH PENERAPAN METODE PEMBELAJARAN SNOWBALL THROWING MENINGKATKAN HASIL BELAJAR SISWA KELAS 4 PEMBELAJARAN MATEMATIKA - Ismayani, Rahma; Kasriman, Kasriman (Academy of Education Journal, 2023)
The purpose of this study was to determine the effect of using the Snowball Throwing learning method on the learning outcomes of students in grade IV SDN Kebon Pala 11 Pagi. This study used a quantitative experiment with a One Group Pretest-Posttest Design. The sample used in this study consisted of 58 students, the samples were taken by random sampling. In this study the data collection techniques were observation, testing and documentation. Then analyzed using an independent sample t test to determine whether there is a relationship between the Snowball Throwing learning method and student learning outcomes. Based on the results of the conclusion, the results of the t-test were obtained, namely tcount > ttable (12,119 > 2,003) with a significance level of 0,05. Based on the results of this study it was concluded that Ho was rejected and H1 was accepted.